Research and training challenges within SmartEN Marie Curie ITN - Onoufriou, Toula; Tantele, Elia; Hadjimitsis, Diofantos G.; Chrysostomou, Christis (My University, 2010)
The research and training challenges of the EU funded SmartEN Marie Curie ITN Program focusing in the area of Smart Management for Sustainable Human Environment are presented in this paper. SmartEN includes the development of an initial research and training network that focuses its activities on the development, effective integration and increased utilization of emerging technologies in wireless sensors, communications and proactive management in the smart management of the human environment. Beyond the specific research challenges in the various individual disciplines involved there are many additional challenges associated with its multi-disciplinary nature and its trans-national and multi-centre research environment. Furthermore, the program addresses many vertical and horizontal research themes, working both at a generic and an application level. The training challenges include the development of a high quality comprehensive and multi-disciplinary training program able to equip the young researchers with world-class scientific knowledge and necessary complementary interpersonal and professional skills, covering a large number of interconnected local and network-wide actions
Keywords: Environmental management; Maintainability (Engineering); Research; Sustainable development